Propuesta complejo habitacional asociado a factores sociales, económicos y culturales en la comuna 4 en la ciudad de Villavicencio. - Gomez Galindo, Laura Valentina (Universidad Antonio Nariño, 2024)
One of the goals that have been set by various political administrations at the national level is to reduce the country's housing deficit. For this work, the city of Villavicencio was chosen, which is no stranger to the country's housing deficit. This city due to its strategic location connects the eastern part with the center of the country and other regions, due to different dynamics of the territory such as internal trade, passage of products, reception of people coming from different areas of the country among others, "the city generated an accelerated and discontinuous growth with various disjointed and empty urban nodes, which represent 7.7% of the current mesh" (PMD, 2020-2023, p. 69)1. According to DANE (2018)2, the quantitative deficit is 15.86% and the qualitative housing deficit in the municipality is 63.72% concepts that will be expanded in the development of the work. A factor that influenced the growth of the municipality were the informal settlements that according to their needs were expanding generating an increase in the demand for housing, goods and services, it is easy to see in the urban fabric of Villavicencio the relationship of selfbuilt or informal housing with planned housing built according to current regulations showing a heterogeneity in the typology, as a result can also be seen the morphological discontinuity of the municipality, which will be discussed later. Taking into account the above at a general level and the results of the analysis developed in this work, we propose a design proposal focused on housing, which integrates social, economic and cultural factors of the community, to provide a flexible design that adapts to the needs of present and future users, which provides a quality of life, is articulated to the various dynamics of the city and incorporates the cultural, social and economic heterogeneity observed in the analysis. Key words: Habitat, Territory, Progressive housing, Adaptive housing, Community.